Evaluation of JNJ-54717793 a Novel Brain Penetrant Selective Orexin 1 Receptor Antagonist in Two Rat Models of Panic Attack Provocation - Bonaventure, Pascal; Dugovic, Christine; Shireman, Brock; Preville, Cathy; Yun, Sujin; Lord, Brian; Nepomuceno, Diane; Wennerholm, Michelle; Lovenberg, Timothy; Carruthers, Nicolas; Fitz, Stephanie D.; Shekhar, Anantha; et al. (Frontiers in Pharmacology, 2017)
Orexin neurons originating in the perifornical and lateral hypothalamic area are highly reactive to anxiogenic stimuli and have strong projections to anxiety and panic-associated circuitry. Recent studies support a role for the orexin system and in particular the orexin 1 receptor (OX1R) in coordinating an integrative stress response. However, no selective OX1R antagonist has been systematically tested in two preclinical models of using panicogenic stimuli that induce panic attack in the majority of people with panic disorder, namely an acute hypercapnia-panic provocation model and a model involving chronic inhibition of GABA synthesis in the perifornical hypothalamic area followed by intravenous sodium lactate infusion. Here we report on a novel brain penetrant, selective and high affinity OX1R antagonist JNJ-54717793 (1S,2R,4R)-7-[(3-Fluoro-2-pyrimidin-2-ylphenyl)carbonyl]-N-[5-(trifluoromethyl)pyrazin-2-yl]-7-azabicyclo[2.2.1]heptan-2-amine). JNJ-54717793 is a high affinity/potent OX1R antagonist and has an excellent selectivity profile including 50 fold versus the OX2R. Ex vivo receptor binding studies demonstrated that after oral administration JNJ-54717793 crossed the blood brain barrier and occupied OX1Rs in the rat brain. While JNJ-54717793 had minimal effect on spontaneous sleep in rats and in wild-type mice, its administration in OX2R knockout mice, selectively promoted REM sleep, demonstrating target engagement and specific OX1R blockade. JNJ-54717793 attenuated CO2 and sodium lactate induced panic-like behaviors and cardiovascular responses without altering baseline locomotor or autonomic activity. These data confirm that selective OX1R antagonism may represent a novel approach of treating anxiety disorders, with no apparent sedative effects.